구매력평가 가설에 대한 연구: 중국을 대상으로 - 장설근; 하육강; Zhang, Xueqin; He, Yugang (International journal of industrial distribution and business, 2019)
Purpose - Along with Chinese exchange rate's reform advancement, the issue of exchange rate of RMB has increasingly become the heated focus in the world. In July 2005, China carried out the reform of the exchange rate system, and this behavior has aroused the attention of the world. However, the dispute on whether the theory of purchasing power parity holds or not in China still exists. As such, this paper will attempt to explore whether the purchasing power parity is significant in China. Research design, data, and methodology - The monthly data from July 2005 to December 2017 will be employed to analyze the nominal exchange rate of RMB against the US dollar and the nominal exchange rate of RMB against the euro. Based on these datum, an empirical analysis will be conducted under the unit root test and the cointegration test to exploit the significance of purchasing power parity in China. Results - The findings of this paper reveal that an increase in China's consumer price index will lead to an increase in the RMB exchange rate, which will lead to the depreciation of RMB. Concomitantly, an increase in the consumer price index in the US and Europe will result in a decrease in the RMB exchange rate, which will lead to an appreciation of RMB. In general, in terms of the US, if US consumer price index increases by 1%, China's nominal exchange rate against US dollar will decrease by 0.905%; if China's consumer price index increases by 1%, China's nominal exchange rate against US dollar will increase by 0.648%. In terms of Europe, if Europe consumer price index increases by 1%, China's nominal exchange rate against euro will decrease by 0.277%; If China's consumer price index increases by 1%, China's nominal exchange rate against euro will increase by 0.235%. Conclusions - Generally speaking, the empirical evidences this paper provided show that the purchasing power parity theory has a certain explanatory ability for the decision of RMB exchange rate. As such, the purchasing power parity cannot hold completely, and China's government should continue to deepen the reform of the exchange rate system to improve China's exchange rate market.